Cardiac Mixoma a Cause of Sudden Death in Childhood a Case Report - Turan, Arzu Akçay; Akyıldız, Elif Ülker; Şahin, Esat; Melez, Deniz Oğuzhan; Pakiş, Işıl; Ersoy, Gökhan (The Bulletin of Legal Medicine, 2009)
The primary tumors of the heart are quite rare and, it’s frequency in the autopsy series is reported between 0,0017-0,28 %. Among the entire age groups, myxomas are seen to form half percent of these tumors. Despite the cardiac myxomas are histologically benign, they are classified among the fatal tumors, causing tendency to cardiac obstruction and embolism. In this study, by examining the history and autopsy findings of a 9 year old sudden death case of which left atrial myxoma is detected in the autopsy; it is aimed to point to cardiac myxomas which can be seen as the cause of sudden death especially in the early ages in the legal autopsies Keywords: Cardiac myxoma, sudden cardiac death, autopsy